Low perinatal zinc status is not associated with the risk of type 1 diabetes in children. Issue 7 (22nd November 2016) - Kyvsgaard, Julie N.; Overgaard, Anne J.; Jacobsen, Louise D.; Thorsen, Steffen U.; Pipper, Christian B.; Hansen, Thomas H.; Husted, Søren; Mortensen, Henrik B.; Pociot, Flemming; Svensson, Jannet
Abstract : Aim: Immunologic events during fetal life may play a part in the pathogenesis of type 1 diabetes (T1D). As zinc is involved in immunologic processes, the purpose was to investigate perinatal zinc status and the later risk of developing T1D and association to age at onset. Methods: A population‐based case–control study based on data from Danish Childhood Diabetes Register and the Danish Newborn Screening Biobank. Cases and controls were matched by birth year and month. Zinc status was analyzed in dried blood spots collected 5 to 7 days after birth. Logistic regression model was used to test the influence of zinc on risk of T1D. Linear regression modeling was used to examine the association between zinc status and covariates as well as age at onset. Zinc status was adjusted for HLA‐DQB1 genotype, birth data and maternal age. Results: Each doubling in perinatal zinc status was not associated with T1D risk; odds ratio (OR) = 1.06 (95% confidence interval [CI] 0.84, 1.32) ( P = 0.62), adjusted for birth year and season. This finding persisted after adjustment for possible confounders; OR = 1.01 (95% CI 0.77, 1.34) ( P = 0.93). In none of the cohorts there were significant associations to age at onset. Conclusion: The risk of developing T1D in Danish children was not associated with perinatal zinc status nor age at onset.